Intercultural Communicative Competence: In-Service EFL Teachers Building Understanding Through Study Groups - Luis Fernando Cuartas Álvarez (Universidad Nacional de Colombia, 2020)
This paper reports on an exploratory collective case study on three in-service English language teachers in Medellin, Colombia. The study aimed at creating a route for teachers to collaboratively construct their understanding of intercultural communicative competence through their involvement in a study group. Data were collected through recordings, interviews, and reflective logs, which followed a bottom-up analysis. Results evidenced changes in the participants' views of culture, cross-cultural knowledge, intercultural stance, and understanding of intercultural communicative competence. As a conclusion, study groups materialized as an applicable tool for teachers' professional development, which allowed participants to redraw their own initial beliefs and assumptions, fostering them to change professionally and in their praxis.